GE_GERICHTE C/12730/2018 vom 2. Dezember 2019 - GE Cour de justice (2019)
OPPOSITION(PROCÉDURE);ORDONNANCE DE SÉQUESTRE;PROTECTION DE L'UNION CONJUGALE;ACQUISITION DE LA PROPRIÉTÉ;OBJET SÉQUESTRÉ;PRINCIPE DE LA TRANSPARENCE(SOCIÉTÉ) | LP.271.al1.ch4; LP.272.al1.ch3; LP.273.al1; LFAIE